Efficacy, safety and mechanistic insights of pentoxifylline in major depressive disorder: a systematic review and meta-analysis of randomized controlled trials - Omar Kassar; NourAllah Farag; Abdullah Selim; Lamees Taman; Menna Alaa; Ahmed Elshahat; Moaz Elsayed Abouelmagd (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Novel treatments that act beyond the conventionally targeted monoamine system are urgently needed to provide more effective relief for patients with major depressive disorder. Pentoxifylline (PTX) is a phosphodiesterase inhibitor with potent anti-inflammatory and antioxidant effects, with additional pleiotropic effects. This is the first systematic review and meta-analysis to examine the role of PTX in major depressive disorder. A comprehensive search of electronic databases, including PubMed, Scopus, Cochrane, and Web of Science, was performed in October 2024. We included only randomized controlled trials (RCTs), and their data were extracted and analyzed using Reman 5.4 software. The primary outcome was the change in Hamilton Depression Rating Scale (HAM-D). Four RCTs with 318 patients were included in the study. PTX showed a statistically significant improvement in HAM-D scores at the primary endpoint compared to the placebo (MD = –3.84, 95% CI [–4.87 to –2.81], P < 0.00001). Moreover, PTX showed a statistically significant increase in serotonin and BDNF levels (MD = 20.76 ng/mL, 95% CI [5.49 to 36.04], P = 0.008; and MD = 10.83 ng/mL, 95% CI [-0.22 to 21.88], P = 0.05, respectively) and a statistically significant decrease in TNF-α and IL-6 levels (MD = –3.24 pg/mL, 95% CI [–4.12 to –2.36], P < 0.00001; and MD = –2.64 pig/mL, 95% CI [–3.79 to –1.48], P < 0.00001, respectively). There was no statistically significant difference between the PTX and placebo in any of the reported side effects. The study findings suggest that PTX may be effective and safe as an adjuvant antidepressant agent in patients with MDD, demonstrating a significant reduction in HAM-D scores. The results of this study need to be interpreted with caution considering several limitations.